Anti‐factor XIII A subunit (FXIII‐A) autoantibodies block FXIII‐A2B2 assembly and steal FXIII‐A from native FXIII‐A2B2. (2nd April 2015) - Souri, M.; Osaki, T.; Ichinose, A.
Summary Background Autoimmune hemophilia‐like disease (hemorrha‐philia or hemorrhagic disorder) caused by anti‐factor XIII antibodies (termed AH13) or 'autoimmune FXIII deficiency' is a life‐threatening bleeding disorder. AH13 was thought to be rare worldwide. Objectives Because the number of diagnosed AH13 cases has recently been increasing, at least in Japan, we conducted a nationwide survey supported by the Japanese Ministry of Health, Labor, and Welfare, and explored the pathologic mechanism(s) of AH13. Methods We diagnosed AH13 cases during the last 11 years according to the presence of anti‐FXIII autoantibodies confirmed by a dot blot assay and ELISA, and characterized 33 of these both immunologically and biochemically. Results The AH13 cases were immunologically classified into three types, Aa, Ab, and B. Type Aa autoantibodies, observed in 27 cases, were directed against the native FXIII A subunit (FXIII‐A), and blocked FXIII activation. The autoantibodies not only prevented assembly of new FXIII‐A2B2 heterotetramers, but also removed FXIII‐A from native FXIII‐A2B2 heterotetramers by forming an FXIII‐A–IgG complex. Type Ab autoantibodies, detected in three cases, preferentially bound to activated FXIII‐A and inhibited its activity. Type Aa and Ab autoantibodies were 'neutralizing' FXIII antibodies (or FXIII inhibitors), and thus could be screened with functional assays. Type B antibodies, detected in two cases, were non‐neutralizing anti‐FXIII B subunit (FXIII‐B) autoantibodies that possibly accelerated the clearance of FXIII, and thus could be diagnosed exclusively with immunologic methods. Conclusion There are three major types of anti‐FXIII autoantibody, with distinct targets and mechanisms that cause AH13.